2008
DOI: 10.1073/pnas.0803174105
|View full text |Cite
|
Sign up to set email alerts
|

Lack of adrenomedullin in the mouse brain results in behavioral changes, anxiety, and lower survival under stress conditions

Abstract: The adrenomedullin (AM) gene, adm, is widely expressed in the central nervous system (CNS) and several functions have been suggested for brain AM. Until now, a formal confirmation of these actions using genetic models has been elusive since the systemic adm knockout results in embryo lethality. We have built a conditional knockout mouse model using the Cre/loxP approach. When crossed with transgenic mice expressing the Cre recombinase under the tubulin T␣-1 promoter, we obtained animals with no AM expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 47 publications
3
53
0
Order By: Relevance
“…Previous studies have shown that a reduction in adm expression results in microtubule hyperpolymerization and higher levels of glu-tubulin in the cell (Sackett et al 2008;Fernandez et al 2008). To check whether this was also the case in aOBSCs, cells from both genotypes were stained with markers for glu-tubulin and the actin cytoskeleton ( Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies have shown that a reduction in adm expression results in microtubule hyperpolymerization and higher levels of glu-tubulin in the cell (Sackett et al 2008;Fernandez et al 2008). To check whether this was also the case in aOBSCs, cells from both genotypes were stained with markers for glu-tubulin and the actin cytoskeleton ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…1) and crossing these animals with transgenic mice that expressed Cre recombinase under the tubulin Tα-1 promoter (Fernandez et al 2008). Heterozygote (w/f Cre + ) mice were crossed and their offspring were genotyped by the polymerase chain reaction (PCR) with tail clip DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that regard, it was recently suggested that vascular damage may be the cause of vascular senescence. 26,27 To test whether these phenomena indicate accelerated senescence, we next evaluated aged conventional RAMP2 KO mice (RAMP2 +/− ). At 2 years of age, RAMP2 +/− mice showed inflammatory cell infiltration of the main organs ( Figure 2G-2I).…”
Section: Severe Vascular Inflammation and Organ Fibrosis In E-ramp2 −mentioning
confidence: 99%
“…Conversely, mice lacking Adm in the brain show overanxious behaviour. 35 Differential expression of ADM has been observed in schizophrenia, 36 and ADM levels have been associated with mood and other psychiatric disorders. [19][20][21] Thus, the biological relevance and the relatively high expression change of Adm in response to paroxetine persuaded us to choose the human homologue of Adm as a candidate gene for genetic association studies in depressed individuals.…”
mentioning
confidence: 99%